High-speed imaging of spray formation and combustion in an optical engine: Effects of injector aging and TPGME as a fuel additive - Zhu, Xinda; Mannazhi, Manu; Palazzo, Natascia; Bengtsson, Per Erik; Andersson, Öivind (Energies, 2020)
High-speed imaging of fuel sprays and combustion is conducted on a light-duty optical engine to investigate the effects of injector aging, with a focus on soot. The spray behaviors of one new and one aged injector are compared using Mie-scattering. In addition to this, the combustion process of a baseline diesel fuel and a blend with TPGME (tripropylene glycol monomethyl ether) are compared using natural luminosity (NL) imaging. TPGME is an oxygenated additive which can be used to reduce soot emissions. X-ray tomography of the two injectors demonstrates that the aging does not lead to significant geometry differences, nor to formation of dense internal nozzle deposits. Both injectors show similar liquid penetration and spreading angle. However, the aged injector shows a prolonged injection and more fuel dribbling after the injection events, leading to a higher injection quantity. The fuel quantity difference shows a larger impact on the NL at low load than the TPGME additive, indicating that the in-cylinder temperature is more important for soot oxidation than oxygen concentration under these conditions. At medium load, the NL is much less sensitive to small temperature variations, while the TPGME is more effiective for soot reduction.
CRIS-Team Scopus Importer:2020-07-24
Keywords: Diesel combustion; Injector aging; Natural luminosity; Spray formation; TPGME

Impact of Oxygenated Additives on Soot Properties during Diesel Combustion - Palazzo, Natascia; Zigan, Lars; Huber, Franz; Will, Stefan (Energies, 2021)
Emissions from diesel engines can be limited and potentially decreased by modifying the fuel chemical composition through additive insertion. One class of additives that have shown to be particularly efficient in the reduction of the particulates from the combustion of diesel fuels are oxygenated compounds. In the present study we investigate the effect of tripropylene glycol methyl ether (TPGME) and two polyoxymethylene dimethyl ethers (POMDME or OMEs) on soot formation in a laminar diesel diffusion flame. From the evaluation of soot volume fraction by laser-induced incandescence (LII) measurements we could observe that OME additives have a substantial capability (higher compared to TPGME) to decrease the particle concentration, which drops by up to 36% with respect to the pure diesel fuel. We also note a reduction in particle aggregate size, determined by wide-angle light scattering (WALS) measurements, which is more pronounced in the case of OME-diesel blends. The effects we observe can be correlated to the higher amount of oxygen content in the OME molecules. Moreover, both additives investigated seem to have almost no impact on the local soot temperature which could in turn play a key role in the production of soot particles.
CRIS-Team WoS Importer:2021-01-29

Investigation of soot formation in a novel diesel fuel burner - Palazzo, Natascia; Kögl, Matthias; Bauer, Philipp; Mannazhi, Manu Naduvil; Zigan, Lars; Huber, Franz; Will, Stefan (Energies, 2019)
In the present work, a novel burner capable of complete pre-vaporization and stationary combustion of diesel fuel in a laminar diffusion flame has been developed to investigate the effect of the chemical composition of diesel fuel on soot formation. For the characterization of soot formation during diesel combustion we performed a comprehensive morphological characterization of the soot and determined its concentration by coupling elastic light scattering (ELS) and laser-induced incandescence (LII) measurements. With ELS, radii of gyration of aggregates were measured within a point-wise measurement volume, LII was employed in an imaging approach for a 2D-analysis of the soot volume fraction. We carried out LII and ELS measurements at different positions in the flame for two different fuel types, revealing the effects of small modifications of the fuel composition on soot emission during diesel combustion.
CRIS-Team Scopus Importer:2019-06-18
Keywords: Elastic light scattering; Fuel comparison; Laser-induced incandescence; Pre-vaporized diesel combustion

Investigation of soot formation in a novel diesel fuel burner - Palazzo, Natascia; Kögl, Matthias; Zigan, Lars; Huber, Franz; Will, Stefan (8th International Workshop on Laser-Induced Incandescence, 2018)

Laser-based investigation of sooting combustion of additized Diesel - Palazzo, Natascia; Zigan, Lars; Huber, Franz; Will, Stefan (International Conference on Advanced Optical Technologies, 2019)

Laser-based investigation of the sooting combustion of additised diesel fuel - Palazzo, Natascia (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2021)